2019
DOI: 10.1186/s12889-019-7419-4
|View full text |Cite
|
Sign up to set email alerts
|

Step-wise approach to prevention of chronic diseases in the Danish primary care sector with the use of a personal digital health profile and targeted follow-up – an assessment of attendance

Abstract: Background Current evidence on chronic disease prevention suggests that interventions targeted at high-risk individuals represents the best way forward. We implemented a step-wise approach in the Danish primary care sector, designed for the systematic and targeted prevention of chronic disease. The intervention centered on a personal digital health profile for all participants, followed by targeted preventive programs for high-risk patients. The present paper examines individual characteristics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
(57 reference statements)
1
32
0
Order By: Relevance
“…A total of 93 high risk patients attended the clinical examination and subsequent health check consultation at their GP. More women, patients with sedentary leisure-time behaviour and patients with low self-efficacy attended the health checks [24]. Sixty patients subsequently answered the CARE and PEI questionnaires and 49 also completed the 3 months follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 93 high risk patients attended the clinical examination and subsequent health check consultation at their GP. More women, patients with sedentary leisure-time behaviour and patients with low self-efficacy attended the health checks [24]. Sixty patients subsequently answered the CARE and PEI questionnaires and 49 also completed the 3 months follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 582 were deemed to be at high risk (group 2) and were offered the targeted intervention at their GP. Another 618 patients engaged in health-risk behaviors (group 3) and were offered the targeted intervention at the MHC [ 28 ]. At 1-year follow-up, 56.2% (327/582) of patients from the high-risk group and 43.9% (271/618) from the health-risk behavior group responded to the questionnaire ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies have found that individuals with low self-e cacy were less likely to participate in general heath checks offered by GPs (31,32). By contrast, in a cross-sectional analysis of participation in a study aimed to prevent T2D, CVD and chronic obstructive pulmonary disease, Larsen et al (33) found that lower selfe cacy was associated with a higher likelihood of getting health checks. We found that self-e cacy per se did not necessarily facilitate participation according to our model, as personal encouragement is also needed.…”
Section: Self-e Cacymentioning
confidence: 99%